Photoautotrophic microorganisms in the glacial ecosystem of Svalbard, high Arctic - Stibal, Marek (Jihočeská univerzita, 2010)
Photoautotrophic microorganisms, i.e. cyanobacteria and microalgae, are ubiquitous in the glacial ecosystem of the high Arctic archipelago of Svalbard. Their communities play significant roles in the ecosystem, including organic carbon production on the glacier surface and its supply to downstream environments, initiating microbial colonisation after glacier retreat and preparing proglacial substrata for further succession.
Photoautotrophic microorganisms in the glacial ecosystem of Svalbard, high Arctic
Keywords: cyanobacteria; algae; glacial ecosystem; microbial colonisation; Svalbard; Arctic; cyanobacteria; algae; glacial ecosystem; microbial colonisation; Svalbard; Arctic